Bilateral Pseudoexfoliation Deposits on Intraocular Lens Implants - Elena Bonafonte Marquez; Sergio Bonafonte Royo (Case Reports in Ophthalmological Medicine)
We present a rare case of bilateral pseudoexfoliative deposits on both intraocular lens (IOL) implants in an 83-year-old woman with no other associated pathology, 5 years after cataract surgery. Pseudoexfoliation syndrome is the most common cause of secondary open-angle glaucoma worldwide and these deposits are usually found on the natural lens. The fact that pseudoexfoliative deposits have been found on IOL implants implies the need for a thorough examination in pseudophakic patients, for it could be the only sign of secondary glaucoma.